Antibacterial activities of selected marine fungi from Peninsular Malaysia / Audra Shaleena A/P Paliany - Paliany, Audra Shaleena (2014)
Over the past few decades, scientists have come to acknowledge the growing importance of marine and marine-related resources for new drugs, pesticides and anti-fouling substances, with over 10,000 metabolites isolated from marine organisms to date. In an effort to tap into the pharmaceutical potential of marine fungi in Malaysia, selected marine derived endophytic and manglicolous fungi from the coastlines of Peninsular Malaysia were investigated for their antibacterial potential. The endophytic fungi in this study were isolated from two marine associated plants; Vitex rotundifolia L.f. and Ipomoea pes-caprae (L.) R.Br., from the east and west coast of Peninsular Malaysia respectively. A total of 13 and 21 endophytic fungi were isolated from V. rotundifolia and I. pes-caprae, respectively. The eleven manglicolous fungi strains used in this study were of mangrove origin and were obtained from the Institute of Biological Sciences (ISB) culture collection. In preliminary experiments, a mycelial plug assay was employed to study the antibacterial activities of both endophytic and manglicolous fungi. Almost 38.5% of the fungal strains from V. rotundifolia and 47.6% of the fungal strains from I. pes-caprae exhibited antibacterial activity against at least one test bacteria. Ten or 91% of the manglicolous fungi exhibited antibacterial activity against at least one test bacteria. Endophytic fungi from I. pes-caprae displayed higher potential for antibacterial activity in comparison to endophytic fungi from V. rotundifolia. Minimidochium sp. and Bipolaris sp. displayed antibacterial activity towards five or more of the test bacteria. Ten or 91% of the eleven manglicolous fungi displayed antibacterial activity. Saccardoella rhizophorae, Henningsomyces sp., Dactylospora haliotrepha (ISB003) and MF 28 exhibited promising antibacterial potential. Based on the results from the mycelial plug assay, five endophytic and ten manglicolous fungi were further investigated using the broth microdilution assay to obtain quantitative antibacterial parameters. Saccardoella rhizophorae was chosen for complete chemical analysis of its secondary metabolite profile. Bioactivity-guided fractionation of S. rhizophorae crude extract resulted in the isolation and characterization of two fatty acids namely palmitic acid and linoleic acid from the n-hexane fraction. Both isolated fatty acids exhibited antibacterial activity against gram positive bacteria. Certain fatty acids are important constituents of essential oils and fatty acids, such as linoleic acid, are important as nutritional supplements. Fatty acids are also essential in the field of biodiesel which is fast becoming the preferred alternate to conventional fuel with research being performed to identify sustainable sources of biodiesel feedstock. The isolation of fatty acids from S. rhizophorae indicates its potential application in the field of food technology and biodiesel. Although Malaysia hosts a great diversity of fungi, there are very few studies on metabolites of fungal origin, thus this study may prove crucial in paving the way towards commercial application of fungal metabolites and possibly lead to further discovery of new or novel fungal metabolites with pharmacological values.